REGALIANVS AND DRYANTILLA RELOADED. THE NEW EVIDENCE FROM CARNUNTUM - Cristian Anton Gazdac (Journal of Ancient History and Archaeology, 2015)
The present work deals with the new numismatic evidence coming from two excavations at the archaeological site of Carnuntum (nowadays, Petronell-Carnuntum, Asutria). Three more coins of the usurper couple of Regalianus and Dryantilla can throw a new light on the location of the mint that issued these coins.